Fast and experimentally validated model of a latent thermal energy storage device for system level simulations. (1st December 2018) - Waser, R.; Ghani, F.; Maranda, S.; O'Donovan, T.S.; Schuetz, P.; Zaglio, M.; Worlitschek, J.
Highlights: Computationally efficient method proposed to characterise latent storage units. Model validated using two different salt hydrate based latent storage devices. Model applicable with analytic equations for effective conductivities. High accuracy proven without calibration. Approach suitable for annual energy system simulations with latent storages. Abstract: Latent storages utilising phase change materials (PCM) to store thermal energy offer a considerably higher energy density at a nearly constant temperature level in comparison to sensible storage systems. Despite this advantage, only a few latent storage technologies have been integrated successfully to the market. This may be due several engineering challenges and in particular the lack of a computationally fast and accurate mathematical model to facilitate the optimal incorporation of latent heat storages into an energy system. The presented study fills this gap and proposes a new, fast and experimentally validated mathematical modelling approach for latent heat storage units. The numerical model proposed combines high accuracy, low computational effort and numerical stability. The validation was performed with two different commercial latent storage units supplied by Sunamp Ltd. with a nominal phase change temperatures of 34 °C and of 58 °C. Both units use a salt hydrate based phase change material in combination with a fin-tube heat exchanger. The proposed model may be used for both fast system level performance investigations as well as latent storage design for a given application. It may therefore be implemented in commercial software packages such as TRNSYS [1] or Simulink [2].